Análises físico-químicas de soluções aquosas: uma abordagem experimental e interdisciplinar como ferramenta impulsionadora da aprendizagem no ensino médio - Benjamin, Glauber Oliveira (2018)
Within the curricular proposal of the Teaching of Chemistry, the second year of High School is characterized as one of the most challenging, because it has concepts often considered as abstract, specifically in the content of solutions, besides requiring the transfer of skills that require the performance of calculations and analysis of graphs. Thus, the present research aimed to investigate the impact of the application of Physics-Chemistry techniques (refractometry, pycnometry, conductimetry and photocolorimetry ) adapted to the teaching of content of solutions, in order to provide a better understanding in the students, based on the action-reflection and the practical application of the concepts in experimental classes. A class of 36 second-year students was used, where half of it served as a control group and the other experienced the content within the approaches presented. At the first moment, a diagnostic evaluation was performed with the students, which served to observe and consider what the students already possessed of luggage, making it possible to divide them into 2 similar groups. The focus of the work was based on a textbook approach, for the control group, during 4 classes, while the experimental group (researched) experienced the content in a practical way, with experimental activities, questioning and data analysis. As a result, it was verified that the physicochemical practices promoted a greater assimilation of chemical concepts, such as solution, solute and solvent, physical quantities such as concentration, density and titre, in addition to stimulating the learning of equation content of the line and its graphs, within the interdisciplinary approach, verified through the final questionnaire applied to the researched class. It is concluded that the techniques of refractometry and pycnometry, when allied, favor substantially the learning and mastery of concepts and procedures pertinent to the study and preparation of solutions, such as the quantities involved. On the other hand, the approach of the equation of the line through the conducymetry and photocolorimetry impel a contextualized and interdisciplinary learning for the teaching of Functions of the 1st Degree, at the same time that also contributes to the assimilation of the chemical concepts, since they dynamize, stimulate and motivate students.